Impairment of Long-Term Plasticity of Cerebellar Purkinje Cells Eliminates the Effect of Anodal Direct Current Stimulation on Vestibulo-Ocular Reflex Habituation - Das, Suman; Spoor, Marcella; Sibindi, Tafadzwa M.; Holland, Peter; Schonewille, Martijn; De Zeeuw, Chris I.; Frens, Maarten A.; Donchin, Opher (Frontiers in Neuroscience, 2017)
Anodal direct current stimulation (DCS) of the cerebellum facilitates adaptation tasks, but the mechanism underlying this effect is poorly understood. We have evaluated whether the effects of DCS effects depend on plasticity of cerebellar Purkinje cells (PCs). Here, we have successfully developed a mouse model of cerebellar DCS, allowing us to present the first demonstration of cerebellar DCS driven behavioral changes in rodents. We have utilized a simple gain down vestibulo-ocular reflex (VOR) adaptation paradigm, that stabilizes a visual image on the retina during brief head movements, as behavioral tool. Our results provide evidence that anodal stimulation has an acute post-stimulation effect on baseline gain reduction of VOR (VOR gain in sham, anodal and cathodal group are 0.75 ± 0.12, 0.68 ± 0.1 and 0.78 ± 0.05 respectively). Moreover, this anodal induced decrease in VOR gain is directly dependent on the PP2B medicated synaptic long-term potentiation and intrinsic plasticity pathways of PCs.